Interest rates and budget deficits: Cross-country evidence from the period 1924-1938 - Matti Virén (Bank of Finland, 1988)
This paper examines the question of whether budget deficits raise nominal interest rates. The empirical analyses make use of cross-country data from 16 countries covering the period 1924 - 1938 .. Contrary to some recent studies (by e.g. Evans), it turns out that budget deficits affect nominal rates positively and thus the Ricardian equivalence proposition can be questioned.
URN:NBN:fi:bof-201807301741
Keywords: 330